Fueling economies through credit and industrial activities. A way of financing sustainable economic development in Brazil - Larissa M. Batrancea; Anca Nichita; Horia Tulai; Mircea-Iosif Rus; Ema Speranta Masca (Green Finance)
As an emerging country preoccupied with preserving its resources for the future, Brazil aims to find the right balance between economic advancement and sustainability goals. In this context, we tackled the link between sustainable economic development and macroeconomic indicators related to domestic credit granted to the private sector, CO2 emissions from industries, and annual inflation rate. By means of time series data analysis run for the period 1996‒2022 via three estimation methods (i.e., least squares, fully modified least squares, dynamic least squares), we found that annual GDP growth rate, control of corruption, and rule of law (as proxies for sustainable economic development) are significantly impacted by GDP growth rate and emissions. Therefore, access to financial resources and intensive industrial activities yielding emissions trigger economic growth, tend to strengthen control of corruption and the rule of law. Additionally, policy implications and future research directions are addressed.